The Political Administrators of Costa Rica at the Time of Independence: Colony or Modernity? - Madrigal Muñoz, Eduardo (2021)
Bureaucracy is a subject of undeniable importance for the understanding of the modern state and for discussions of the political agenda. However, the social composition of bureaucrats is a subject very little discussed in historiography. This work aims to carry out an analysis of the social composition and life careers of individuals who held positions of hierarchy in the political institutions of Costa Rica at the time of independence. This is intended to achieve a deeper understanding of the nature and mechanisms of operation of the first political institutions established in the nascent country after the process of Independence.